Effects of microplastics and nitrogen deposition on soil multifunctionality, particularly C and N cycling - Zhang, Shuwu; Pei, Lei; Zhao, Yanxin; Shan, Jun; Zheng, Xuebo; Xu, Guangjian; Sun, Yuhuan; Wang, Fayuan (Journal of hazardous materials, 2023)
Both nitrogen deposition (ND) and microplastics (MPs) pose global change challenges. The effects of MPs co-existing with ND on ecosystem functions are still largely unknown. Herein, we conducted a 10-month soil incubation experiment to explore the effects of polyethylene (PE) and polylactic acid (PLA) MPs on soil multifunctionality under different ND scenarios. We found that the interactions between ND and MPs affected soil multifucntionality. FAPROTAX function prediction indicated that both ND and MPs affected C and N cycling. ND increased some C-cycling processes, such as cellulolysis, ligninolysis, and plastic degradation. MPs also showed stimulating effects on these processes, particularly in the soil with ND. ND significantly decreased the abundance of functional genes NifH, amoA, and NirK, leading to inhibited N-fixation, nitrification, and denitrification. The addition of MPs also modified N-cycling processes: 0.1% PE enriched the bacterial groups for nitrate reduction, nitrate respiration, nitrite respiration, and nitrate ammonification, and 1% PLA MPs enriched N-fixation bacteria at all ND levels. We found that ND caused lower soil pH but higher soil N, decreased bacterial diversity and richness, and changed the composition and activity of functional bacteria, which explains why ND changed soil functions and regulated the impact of MPs. [Display omitted] •Combined effects of MPs and ND on soil multifunctionality were first explored.•Both MPs and ND changed soil bacterial communities and their functions.•Both MPs and ND modified soil multifunctionality, particularly C and N cycling.•The effects of MPs varied with the type and dose of MPs and the ND levels.•ND enriched the functional bacteria for plastic degradation.